Application of ISO 13606 Archetypes for an Integration of Hospital and Laboratory Information Systems; Communications in Computer and Information Science; Vol. 538 : Information and Software Technologies - Kopanitsa G. D. Georgy Dmitrievich (2015, 2015)
Title screen